Seasonal Activity of a Ground-Beetle (Coleoptera: Carabidae) Assemblage in a remnant of a Salty-Lake from Terceira (Azores). - Borges, Paulo A. V. (1995)
Ground-beetle species were sampled on the remnant of a salty-lake from Terceira (Azores) during one year using pitfall trapping. Three strongly hygrophilous species were found to be dominant: Notaphus (s. str.) semipunctatus (Donavan, 1806), Omaseus aterrimus nigerrimus Dejean, 1828 and Agonum marginatum (Linnaeus , 1758). The former and top dominant one, N. semipunctatus, is a new record for the Azores and Macaronesia. The activity density peak of these dominant species occurred in July. Thus, a «spring-breeder» ground-beetle guild was found to be characteristic of this heterogeneous sally biotope.